Genetically predicted levels of circulating cytokines and prostate cancer risk: A Mendelian randomization study. Issue 9 (12th August 2020) - Sun, Xiaohui; Ye, Ding; Du, Lingbin; Qian, Yu; Jiang, Xia; Mao, Yingying
Abstract: Inflammation is considered to play a pivotal role in the pathogenesis of cancer, and observational studies have reported a relationship between circulating inflammation markers and the risk of prostate cancer. Using summary data of >140 000 individuals, two‐sample Mendelian randomization (MR) analyses were performed to evaluate whether circulating levels of 27 cytokines and growth factors have a causal effect on the risk of developing prostate cancer. Genetically predicted elevated levels of monocyte chemotactic protein‐1 (MCP‐1) were associated with an increased risk of prostate cancer (odds ratio (OR) per 1 SD increase = 1.06, 95% confidence interval (CI): 1.04‐1.09) at Bonferroni‐adjusted level of significance ( P < 1.85 × 10 −3 ). Results were stable across sensitivity analyses, and there was no evidence of directional pleiotropy. Under MR assumptions, our findings suggested a risk‐increasing effect of circulating MCP‐1 levels on prostate cancer. Whether targeting MCP‐1 or its downstream effectors are useful in reducing prostate cancer incidence needs further investigation. Abstract : What's new? Observational studies have reported a relationship between circulating inflammation markers and the risk of prostate cancer. However, these studies cannot exclude potential confounders due to the nature of their traditional design. Here, the authors first performed two‐sample Mendelian randomisation analysis to investigate the potential causal effects of 27 cytokines and growth factors on prostate cancer risk. The results suggested that genetically‐predicted, life‐long elevated levels of circulating monocyte chemotactic protein‐1 (MCP‐1) were associated with a higher risk of prostate cancer. The finding provides supportive evidence of a causal association and hints at MCP‐1 as a potential therapeutic target for prostate cancer.